Diamonds and Toads - Perrault,Charles (37 pages, 2013)
Diamonds and Toads or Toads and Diamonds is a French fairy tale by Charles Perrault, and titled by him "Les Fées" or "The Fairies". Andrew Lang included it in The Blue Fairy Book. It was illustrated by Laura Valentine in Aunt Louisa's nursery favourite.